A mixture of vegetable extracts (chamomile, passionflower, caraway, fennel) and enzymes (beta-galactosidase) for Irritable Bowel Syndrome (IBS): an observational study ("BIOVES"): STUDIO "BIOVES" - Tomasello, Giovanni; Palumbo, Vincenzo Davide; Sinagra, Emanuele; Mazzola, Margherita; Accardo, Agostino; Busalacchi, Andrea; Ciulla, Antonio; Di Trapani, Benedetto; Pirrotta, Paolo; Tomasini, Simone; De Luca, Bartolo; Cusimano, Simona; et al. (Progress in Nutrition, 2018)
Aims: Irritable bowel syndrome (IBS) is a functional intestinal disorder. This syndrome may creates psychological disorders in patients who are affected and severely limits daily activities and lifestyle. Methods: We investigated the effect of the natural product consisting of chamomile, fennel, caraway, passionflower and melissa (Spasmicol®), on IBS patients. For the study, 187 patients with IBS, enrolled by primary care doctors, were treated with Spasmicol® (Aristeia Farmaceutici s.r.l.), two tablets/daily, for 30 days. At the end of the study, patients were re-evaluated to analyse the effects of therapy. Results: After 30 days, patients showed a marked reduction of symptoms (abdominal pain, abdominal distention, stool habit changes). Conclusions: Due to to the combination of chamomile, fennel, caraway, melissa, passionflower and beta-galactosidase, the product Spasmicol® turned out to be remarkedly effective in treating IBS symptoms.